Flagella - Templates for the Synthesis of Metallic Nanowires - Deutscher, Linda; Renner, L. D.; Cuniberti, Gianaurelio (Giovanni) (IFMBE Proceedings, 2014)
The classical approach to synthesize nanowires is based on deposition of conductive metal ions. In this report we present the modification of bacterial appendages in order to form nanowires from renewable biological structures, bacterial flagella. Flagella have many advantageous characteristics of proteinaceous constructs: they possess the ability to self-assemble, to extend over several micrometers in length and possess diameters of 10-20 nm making them ideal candidates for nanowires. We show the isolation of micrometer-sized flagella from three different bacterial strains: Pseudomonas fluorescens, Lysinibacillus sphaericus and Shewanella oneidensis. The dimensions and characteristics of the isolated flagella were investigated by atomic force microscopy and scanning electron microscopy. The bacterial appendages had an average length of approximately 3.7 μm and an average diameter of 10.6 nm. In order to achieve conductive nanowires we applied a methodology to metallize purified flagella. Our results show the applicability of bacterial flagella as scaffolds for nanowire synthesis. We envision that our approach will enable the application of bacterial nanowires to a wide range of biomolecular sensors. © Springer International Publishing Switzerland 2014.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Biotemplating; Flagella; Lysinibacillus sphaericus; Nanowire; Pseudomonas fluorescens; Shewanella oneidensis